A single-center experience of post-transplant lymphoproliferative disorder (PTLD) cases after pediatric liver transplantation: Incidence, outcomes, and association with food allergy - Barış, Zeren; Özcay, Figen; Yılmaz Özbek, Özlem; Haberal, Nihan; Sarıalioğlu, Faik; Haberal, Mehmet (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: We evaluated our 16-year single-center experience of pediatric post-transplant lymphoproliferative disorder (PTLD) cases who underwent liver transplantation between 2001 and 2017. Materials and Methods: Of the 236 pediatric patients who underwent liver transplantation between 2001 and 2017, the clinical and laboratory data of eight patients diagnosed with PTLD were reviewed. The pre-transplant Epstein-Barr virus (EBV) status of 172 patients was also recorded. Results: The total incidence of PTLD was 3.4%. The incidence of PTLD was 10% in pre-transplant EBV immunoglobulin G (IgG)-seronegative patients and 0.8% in pre-transplant EBV IgG-seropositive patients. The mean age of the patients at liver transplantation was 2.71±3.21 years, and four patients were aged below 1 year at the time of transplantation. PTLD was diagnosed at 21.81±18.1 months after transplantation. The primary site of involvement was variable among patients: peripheral and mediastinal lymph nodes, stomach and intestine, transplanted graft, bone marrow, and nasopharynx. The eosinophil count varied greatly among patients, with a mean value of 524.62±679/mm3. Three patients had a food allergy and were administered an elimination diet at the time of PTLD diagnosis. Six patients had PTLD of B-cell origin. One patient died due to neutropenic sepsis during chemotherapy, whereas seven patients were followed up in full remission for 7.75±4 years. Conclusion: PTLD is a life-threatening complication of solid-organ transplantation with a heterogeneous clinical spectrum. Food allergy had a close association with PTLD. A close follow-up of patients with risk factors and an early diagnosis with appropriate treatment may lead to a better outcome. Cite this article as: Barış Z, Özçay F, Yılmaz Özbek Ö, Haberal N, Sarıalioğlu F, Haberal M. A single-center experience of post-transplant lymphoproliferative disorder (PTLD) cases after pediatric liver transplantation: Incidence, outcomes, and association with food allergy. Turk J Gastroenterol 2018; 29: 354-60.